Spycatcher : The Candid Autobiography of a Senior Intelligence Officer - Wright, Peter; Greengrass, Paul (Rawalpindi Army Education Press, 1991)
A rare inside glimpse of the real day-by-day goings-on within the British intelligence world from a high-level authoritative voice.
Include Glossary and Index.
It is a biography.
Keywords: Great Britain -- Intelligence officers -- Wright, Peter, 1916-1995 -- Great Britain, MI5 -- Espionage -- Intelligence service -- Great Britain, MI6 -- Wright, Peter